Changes in Technological Payment Systems in Banking Sector of India - Iman Shrestha (International Journal of Advanced Science and Technology, 2020)
This paper studies the changes in technology in the banking industry in India with the introduction of electronic payment instruments like RTGS Transfers, NEFT, Mobile Banking, etc. India is moving towards digitalization and the government is aiming to make the economy ‘Cashless’. Such changes in technology have brought a radical shift of banking converting from Mass to Class, which has changed the whole banking industry. Globalization, economic development, and, demonetization is some of the major reasons for this upbringing of technologies. With the arrival of foreign and private financial institutions, the increment in competition has also contributed to the development of electric fund transfer tools. Real-Time Gross Settlement (RTGS), NEFT, Mobile banking are some of the technology that has enabled financial institutions in transacting money, making & receiving payments in real-time and more secure. Such advancement in technology has enabled banks to grow and contribute to enabling financial inclusion even more in the country. In the present era, for the economy to move towards being ‘cashless’, institutions like Reserve Bank of India and National Payments Corporation of India have introduced many digital products such as NEFT, RTGS, IMPS, UPI, Mobile Banking, CTS, etc. that offer many options for online transaction and transfers to customers. Some pros of such techs are reduction of operational costs for banks, reduction of transactional costs for customers, better customer services, increment in overall efficiency, etc. After Demonetization, the usage of digital payments spiked throughout the country and some new tools like IMPS, UPI were introduced by the government. Smartphones are now one of the most used devices for making payments as well as receiving them. This has helped in creating a payment system that is uniform and affordable too. Here, the development of technology has created a new platform for enabling financial inclusion even more. As the nation is moving towards becoming digital and with all these platforms to make it all possible, the vision of the Government of India to transform India into a society that is digitally empowered. For India to become “Faceless, Paperless, and Cashless”, such technologies mentioned above happen to be very important. In this study, the yearly volume transactions of RTGS and Mobile banking transactions of the years 2013 to 2019 of all the banks listed in the Reserve Bank of India’s Bulletin have been used as data samples and those data have been analyzed using Paired T-tests, and Shapiro-Wilk Test of Normality. This study concludes that the strategy of banks of shifting from a high-cost transactional Centre to a wide range of service providers such as e-banking, digital wallets, ATMs, Kiosks, etc. and also concludes that digital payments through mobile have significantly increased after demonetization.